2017
DOI: 10.1515/nanoph-2017-0030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on the structural, linear, and nonlinear optical properties of MgO-doped graphene oxide nanocomposites

Abstract: Magnesium oxide (MgO)-graphene oxide (GO) nanocomposites were prepared by the hydrothermal method at different temperatures. The effect of growth temperature on the structural, linear, and nonlinear optical (NLO) parameters was investigated. The decoration of MgO on GO sheets was confirmed by X-ray diffraction, scanning electron microscopy, Fourier transform infrared, and UV-visible (UV-vis) spectroscopy analyses. The energy band-gaps of MgO-GO nanocomposites were calculated from UV-vis spectrum using Tauc plo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“… 16 The report has established the impact of oxidation leads to a variation in the energy gap. 40 The non-uniform variation in the oxidation content of GO and GO:Fe 2 O 3 and the double transitions of the π–π and n–π in the absorption account for the variational energy gaps. 41 …”
Section: Resultsmentioning
confidence: 99%
“… 16 The report has established the impact of oxidation leads to a variation in the energy gap. 40 The non-uniform variation in the oxidation content of GO and GO:Fe 2 O 3 and the double transitions of the π–π and n–π in the absorption account for the variational energy gaps. 41 …”
Section: Resultsmentioning
confidence: 99%
“…Consequently, this energy difference facilitates photon-induced transitions between the π and π* orbitals. The initial peak corresponds to the π-π* transition of the C=C bond, while the subsequent peak corresponds to the n-π* transition involving the carbonyl (C=O) bonds of GO [42].…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, this energy difference facilitates photon-induced transitions between the π and π* orbitals. The initial peak corresponds to the π-π* transition of the C=C bond, while the subsequent peak corresponds to the n-π* transition involving the carbonyl (C=O) bonds of GO [42]. The nonlinear absorption behavior of GO nanoflakes in DI water was characterized through an open z−scan technique, revealing normalized nonlinear transmittance as a function of sample position (z) across various peak excitation intensities, namely ~6.4 GW/cm 2 , 3.5 GW/cm 2 , 1.9 GW/cm 2 , 1.1 GW/cm 2 , and 0.1 GW/cm 2 at the focal plane (refer to Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the catalytic ozonation significantly improved the mineralization of phenol compared to that without the catalyst. In parallel the hydrothermal method was followed by Kimiagar et al 213 to combine MgO with GO. The effect of growth temperature on the structural, linear, and nonlinear optical (NLO) parameters was investigated.…”
Section: Go–metal Oxide (Mo) Based Nanocompositesmentioning
confidence: 99%